Ljubljana's Food Supply 1941-1945 Preskrba Ljubljane s hrano 1941-1945 - Šorn, Mojca (Inštitut za novejšo zgodovino, 2008)
After the occupation, the citizens of Ljubljana found themselves in a difficult situation as far as their food supply was concerned. At that time, the new state border cut off Ljubljana's economic hinterlands from the city, which only had modest reserves at its disposal, and it, overrun by thousands of refugees, lost its last remaining link with the surroundings after it had been encircled in barbed wire. The authorities attempted to alleviate the distress of the people with various measures, and at the same time they advised them to help themselves in the struggle for survival. Despite all efforts, the city's isolation and the consequences of war called for the increasingly strict rationing or even cancellation of more and more basic necessities of life, and the prices went up. Thus in the final months of the occupation, the metropolis saw starvation. Malnutrition manifested itself in poor health conditions and a high mortality of tuberculosis patients. Glede preskrbe so se po okupaciji Ljubljančani znašli v nezavidljivem položaju. Takrat je nova državna meja od Ljubljane, ki je razpolagala le s skromnimi zalogami, odrezala njeno gospodarsko zaledje, zadnjo vez z okolico pa je mesto, preplavljeno s tisoči beguncev, izgubilo po obžičenju (februarja 1942). Oblasti so stisko ljudi poskušale reševati z različnimi ukrepi, hkrati pa so jim svetovale, naj si v boju za preživetje pomagajo tudi sami. Kljub vsemu so izolacija mesta in posledice vojne terjale racioniranje vse več osnovnih življenjskih potrebščin ter nižanje ali celo izostanke in višanje cen kontingentov le-teh. Zadnji meseci okupacije so v prestolnici tako potekali v znamenju lakote. Nezadostna prehrana se je odražala v slabem zdravstvenem stanju in visoki smrtnosti obolelih za tuberkulozo.